Battery cell, battery device, power consuming device, and energy storage device
Patent Information
- Application Number
- CN202510404797.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2026-10-16
AI Technical Summary
[0061] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below.
Smart Images

Figure CN122930833A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery cell technology, and in particular to a battery cell, battery device, power consumption device and energy storage device. Background Technology
[0002] In recent years, battery cells have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power plants, as well as in many fields such as power tools, electric bicycles, electric motorcycles, electric cars, military equipment, and aerospace.
[0003] As the market demands for longer driving range and faster charging performance of electrical devices, higher requirements are being placed on the cycle performance and dynamic performance of individual battery cells. However, existing technologies struggle to simultaneously improve these performance characteristics, making this a pressing technical problem that needs to be solved in this field. Summary of the Invention
[0004] This application is made in view of the above-mentioned issues, and its purpose is to provide a battery cell that has both good fast charging performance and high cycle performance.
[0005] The first aspect of this application provides a battery cell, including a positive electrode, a negative electrode, and an electrolyte; the negative electrode includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the negative electrode film layer includes a negative electrode active material, the negative electrode active material includes microcrystalline graphite, and the particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 0.5-3.
[0006] Natural flake graphite or artificial graphite has a primary particle size greater than 5 μm, with orderly layered arrangement and anisotropy. Microcrystalline graphite, unlike natural flake graphite and artificial graphite, exhibits an amorphous or cryptocrystalline structure with a more disordered layered arrangement, thus possessing isotropy, which is beneficial for the uniform insertion of lithium ions from all directions. Unlike existing technologies, the battery embodiments of this application use microcrystalline graphite as the negative electrode active material. Utilizing the isotropic characteristics of microcrystalline graphite, it increases the effective end faces for lithium ion insertion and extraction, thereby further improving the kinetic performance of the battery cell.
[0007] However, microcrystalline graphite has a wide particle size distribution, and particles of varying sizes easily combine to form dense packings. During cycling, this makes it easy for the electrolyte to be squeezed out, and the recirculation rate is slow, leading to a decrease in battery capacity retention and deterioration of battery cycle stability. In the embodiments of this application, the negative electrode active material includes microcrystalline graphite, and the particle size distribution (Dv90-Dv10) / Dv50 is controlled within the range of 0.5-3, resulting in more uniform microcrystalline graphite size, reducing electrolyte loss, and improving battery cycle performance. Simultaneously, the more uniform size of the microcrystalline graphite helps increase the porosity of the negative electrode film, improving electrolyte wetting and reabsorption, further enhancing the battery's fast-charging performance.
[0008] In any embodiment, the particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 0.5-2.
[0009] In this embodiment, the particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is controlled within the above range. The size of the microcrystalline graphite is more uniform, and the porosity of the negative electrode film containing microcrystalline graphite is increased, which helps to further improve the cycle performance and fast charging performance of the battery cell.
[0010] In any embodiment, the orientation degree (OI) of the microcrystalline graphite is 0.5-4.
[0011] When the OI value of microcrystalline graphite is within the above range, the degree of order of microcrystalline graphite is low, and the content of effective end faces for lithium ion insertion and extraction is high, which is conducive to the uniform insertion of lithium ions from all directions, improves the dynamic performance of the electrode, and enhances the fast charging performance of the battery.
[0012] In any embodiment, the orientation degree (OI) value of the microcrystalline graphite is 2-3.
[0013] A high OI value indicates high internal grain order, reducing the effective end faces for lithium-ion insertion / extraction, leading to decreased electrode kinetics and consequently affecting the battery's fast-charging performance. Conversely, a low OI value indicates low internal grain order, increasing side reactions between disordered carbon materials and the electrolyte, thus affecting the battery's cycle performance. In the embodiments of this application, the OI value of the microcrystalline graphite is in the range of 2-3, indicating suitable internal grain order, which helps improve the battery's fast-charging performance while maintaining good cycle performance.
[0014] In any embodiment, the volume distribution particle size Dv99 of the microcrystalline graphite is 20-50 μm, and the volume distribution particle size Dv50 of the microcrystalline graphite is 10-25 μm.
[0015] In any embodiment, the volume distribution particle size Dv99 of the microcrystalline graphite is 20-50 μm, and the volume distribution particle size Dv50 of the microcrystalline graphite is 10-20 μm.
[0016] Furthermore, in the embodiments of this application, the Dv50 of the microcrystalline graphite is in the range of 10-20 μm. The reduction in particle size and the increase in specific surface area of the particles help to provide more active sites and shorten the insertion / extraction path, thereby improving the insertion / extraction speed, improving the kinetic performance of the negative electrode sheet, and further improving the fast charging performance of the battery.
[0017] In any embodiment, the graphitization degree of the microcrystalline graphite is greater than or equal to 88%.
[0018] In any embodiment, the graphitization degree of the microcrystalline graphite is 90%-96%.
[0019] Graphitization degree reflects the integrity of the graphite crystal structure in a material, that is, the regularity of the arrangement of carbon atoms in the graphite structure. High graphitization degree indicates small interlayer spacing, smaller lattice rotation, less random stacking of layers, and a more ordered arrangement, resulting in high specific capacity. Low graphitization degree indicates large interlayer spacing, which is beneficial for rapid lithium-ion insertion / extraction, improving the rate performance of the battery. Furthermore, large interlayer spacing results in less material expansion during lithium insertion, leading to a shallow charge / discharge effect. Additionally, low graphitization degree reduces the amount of splined carbon atoms in the graphite material. 3 The abundance of bonds in graphite materials creates inter-layer constraints, resulting in a more stable structure and excellent stability during cycling, which is beneficial for long-term cycling. In the embodiments of this application, the degree of graphitization of the microcrystalline graphite is within the above-mentioned range, which is beneficial for improving the cycle performance of the battery cells.
[0020] In some implementations, the oil absorption value of microcrystalline graphite is less than or equal to 65.
[0021] In some implementations, the oil absorption value of microcrystalline graphite is 55-60.
[0022] The oil absorption value of a material is mainly related to its specific surface area, surface properties, particle shape, and particle size distribution. The oil absorption value of the negative electrode active material reflects its dispersibility in the negative electrode slurry. A low oil absorption value indicates excellent dispersibility in the negative electrode slurry, resulting in superior anti-settling and dispersibility properties. This facilitates control of the coating weight during electrode coating, leading to the preparation of negative electrode sheets with uniform distribution and thickness of the active material. It also reduces the possibility of uneven local current density during charging and discharging, minimizes lithium plating caused by electrode polarization, and improves battery cycle performance. In conclusion, microcrystalline graphite with a suitable oil absorption value range is beneficial for improving the cycle performance of individual battery cells.
[0023] In any embodiment, the negative electrode film layer includes a first negative electrode film layer disposed near the negative electrode current collector side and a second negative electrode film layer disposed away from the negative electrode current collector side of the first negative electrode film layer. The first negative electrode film layer includes a first negative electrode active material, which includes microcrystalline graphite with a particle size distribution (Dv90-Dv10) / Dv50 of 0.5-3.
[0024] Microcrystalline graphite exhibits superior lithium intercalation kinetics due to its isotropic properties. Placing a first negative electrode film containing microcrystalline graphite on the current collector side helps increase the driving force for lithium ions to migrate from the electrolyte to the current collector side, improves the diffusion rate and reabsorption rate of lithium ions in the negative electrode film, and enhances the battery's kinetic performance and cycle stability.
[0025] In any embodiment, the porosity of the first negative electrode film layer is 12%-30%.
[0026] In any embodiment, the porosity of the first negative electrode film layer is 18%-28%.
[0027] The negative electrode film layer near the current collector typically has a lower electrolyte wetting rate, thereby reducing the contact area between the electrolyte and the negative electrode active material and affecting the battery's fast-charging performance. In this embodiment, the first negative electrode film layer is close to the current collector and has a higher porosity, which helps to improve the electrolyte wetting rate of the negative electrode film layer near the current collector, thereby improving the battery's fast-charging performance.
[0028] In any embodiment, the OI value of the first negative electrode film is 1-4.
[0029] The OI value indicates the degree of order in the arrangement of crystals or particles in a material. A higher OI value indicates a more ordered arrangement of particles or molecules in the material; a lower OI value indicates a more disordered orientation of the material. The OI value of the first negative electrode film layer in the embodiments of this application is within the above range, and the disorder of the first negative electrode film layer is low, which helps to increase the number of lithium-ion insertion / extraction end faces, improve the dynamic performance of the electrode, and thus improve the fast charging performance of the battery.
[0030] In any embodiment, the OI value of the first negative electrode film is 2-3.
[0031] A high OI value indicates high material order, fewer effective lithium-ion insertion / extraction faces, and decreased electrode kinetics, thus affecting the battery's fast-charging performance. Conversely, a low OI value indicates low material order, high porosity of the negative electrode film, increased electrolyte wetting, and increased side reactions, thus affecting the battery's cycle performance. In the embodiments of this application, the orientation degree OI value of the first negative electrode film is in the range of 2-3, indicating suitable material order, which helps improve the battery's fast-charging performance while also ensuring good cycle performance.
[0032] In any embodiment, the second negative electrode film layer includes a second negative electrode active material, which includes one or more of natural flake graphite and artificial graphite.
[0033] In any embodiment, the second negative electrode film layer includes a second negative electrode active material, which includes artificial graphite.
[0034] In any embodiment, the second negative electrode film layer includes a second negative electrode active material, which includes natural flake graphite.
[0035] Natural flake graphite and artificial graphite have good cycle stability. The second negative electrode film layer in the embodiments of this application includes one or more of natural flake graphite or artificial graphite, which helps to further improve the cycle performance of the battery.
[0036] In any embodiment, the orientation degree OI value of natural flake graphite is 4.5-10.
[0037] In any embodiment, the orientation degree (OI) value of the artificial graphite is 5-12.
[0038] If the orientation degree (OI) value of natural or artificial graphite is within the above range, it indicates that it is anisotropic compared to microcrystalline graphite, which is not conducive to lithium ion insertion from all directions, but can improve battery capacity.
[0039] In any embodiment, the volume distribution particle size Dv50 of the second negative electrode active material is 8-25 μm.
[0040] In any embodiment, the volume distribution particle size Dv50 of the second negative electrode active material is 10-20 μm.
[0041] In any embodiment, the volume distribution particle size Dv99 of the second negative electrode active material is 25-45 μm.
[0042] In any embodiment, the volume distribution particle size Dv99 of the second negative electrode active material is 27-40 μm.
[0043] The volume distribution particle size of the second negative electrode active material is within the above range (Dv50, Dv99), and the battery cell has good fast charging performance and energy density.
[0044] In any embodiment, the porosity of the second negative electrode film is 15%-25%.
[0045] In any embodiment, the porosity of the second negative electrode film is 17%-24%.
[0046] Controlling the porosity of the second negative electrode film within the above range can match the porosity of the first negative electrode film while taking into account the capacity of the negative electrode film, which helps to improve the fast charging performance of the battery while also taking into account the energy density.
[0047] In any embodiment, the OI value of the second negative electrode film is 5-13.
[0048] In any embodiment, the OI value of the second negative electrode film is 5-10.
[0049] In any embodiment, the thickness ratio of the first negative electrode film layer and the second negative electrode film layer is 2:8-5:5.
[0050] In any embodiment, the thickness ratio of the first negative electrode film layer and the second negative electrode film layer is 4:6-5:5.
[0051] In this embodiment, controlling the thickness ratio of the first negative electrode film layer and the second negative electrode film layer within the above-mentioned range helps to improve the fast charging performance of the battery, while also helping to balance cycle performance and energy density.
[0052] In any embodiment, the thickness of the negative electrode film is 80-160 μm.
[0053] In any embodiment, the thickness of the negative electrode film is 100-150 μm.
[0054] In this embodiment of the application, when the ratio of the single-sided thickness of the negative electrode film to the thickness of the negative electrode current collector is within the above range, the fast charging performance of the battery can be further improved while taking into account the energy density.
[0055] In any embodiment, the compaction density of the negative electrode film layer in the fully discharged state of the battery cell is 1.6 g / cm³. 3 -1.85g / cm 3 .
[0056] In any embodiment, the compaction density of the negative electrode film layer in the fully discharged state of the battery cell is 1.65 g / cm³. 3 -1.75g / cm 3 .
[0057] When a battery cell is fully discharged, the compaction density of the negative electrode film is within the above-mentioned range, which is beneficial to improving the energy density of the battery cell.
[0058] A second aspect of this application provides a battery device, which includes the battery cell provided in the first aspect.
[0059] A third aspect of this application provides an electrical device, which includes the battery device provided in the second aspect, the battery device being used to provide electrical energy.
[0060] The fourth aspect of this application provides an energy storage device, which includes the battery device provided in the second aspect, the battery device being used to store electrical energy.
[0061] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, specific embodiments of this application are given below. Attached Figure Description
[0062] In the accompanying drawings, unless otherwise specified, the same reference numerals throughout the various drawings denote the same or similar parts or elements. These drawings are not necessarily drawn to scale. It should be understood that these drawings depict only some embodiments disclosed in this application and should not be construed as limiting the scope of this application.
[0063] Figure 1 This is an electron microscope image of the microcrystalline graphite.
[0064] Figure 2 This is an electron microscope image of the morphology of artificial graphite;
[0065] Figure 3 This is a schematic diagram of a battery cell provided in some embodiments of this application;
[0066] Figure 4 This is a schematic diagram of a battery module provided in some embodiments of this application;
[0067] Figure 5 This is a schematic diagram of a battery pack provided in some embodiments of this application;
[0068] Figure 6 yes Figure 5 An exploded view of the battery pack shown.
[0069] Figure 7 This is an exploded view of a single battery cell provided in some embodiments of this application;
[0070] Figure 8 This is a schematic diagram of an electrical device provided in some embodiments of this application.
[0071] The accompanying drawings are not necessarily drawn to scale.
[0072] Explanation of reference numerals in the attached diagram: 1. Battery pack; 2. Upper casing; 3. Lower casing; 4. Battery module; 5. Battery cell; 51. Housing; 52. Electrode assembly; 53. Cover plate. Detailed Implementation
[0073] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided for the purpose of enabling those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0074] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0075] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0076] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0077] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0078] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0079] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0080] In this application, the terms "multiple" or "various" refer to two or more kinds of things.
[0081] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0082] Unless otherwise stated, the values of the parameters mentioned in this application can be obtained using various testing methods commonly used in the art.
[0083] The measurements can be performed, for example, according to the test methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.
[0084] The battery mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules, or battery packs.
[0085] A battery cell is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. A battery cell can be cylindrical, cuboid, or other shapes, and the embodiments of this application are not limited in this respect. Figure 3 The example shown is a rectangular battery cell 5.
[0086] When there are multiple battery cells, they are connected in series, parallel, or mixed via a busbar. In some embodiments, the battery can be a battery module; when there are multiple battery cells, they are arranged and fixed to form a battery module. In some embodiments, the battery can be a battery pack, which includes a housing and battery cells, with the battery cells or battery modules housed within the housing. In some embodiments, the housing can be part of the vehicle's chassis structure. For example, a portion of the housing can be at least part of the vehicle's floor, or a portion of the housing can be at least part of the vehicle's crossbeams and longitudinal beams.
[0087] In some embodiments, the battery can be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.
[0088] In some embodiments, individual battery cells can be assembled into a battery module, and the number of individual battery cells contained in the battery module can be multiple, the specific number of which can be adjusted according to the application and capacity of the battery module. Figure 4This is a schematic diagram of battery module 4 as an example. Figure 4 As shown, in battery module 4, multiple battery cells 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple battery cells 5 can be fixed in place using fasteners.
[0089] Optionally, the battery module 4 may also include a housing with a receiving space in which multiple battery cells 5 are received.
[0090] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0091] Figure 5 and Figure 6 This is a schematic diagram of battery pack 1 as an example. Figure 5 and Figure 6 As shown, the battery pack 1 may include a housing and multiple battery modules 4 disposed within the housing. The housing includes an upper housing 2 and a lower housing 3. The upper housing 2 covers the lower housing 3, forming a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the housing.
[0092] The battery provided in this application embodiment may include a lithium-ion battery.
[0093] A single battery cell includes an electrode assembly and an electrolyte. The electrode assembly can be a wound structure or a stacked structure, and the embodiments of this application are not limited in this regard.
[0094] The battery cell may also include an outer packaging, which can be used to encapsulate the electrode components and electrolyte. The outer packaging can be a rigid shell, such as a hard plastic shell, aluminum shell, or steel shell. The outer packaging can also be a flexible package, such as a pouch-type flexible package. The material of the flexible package can be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0095] In some embodiments, such as Figure 7 As shown, the outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates enclosing a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 is used to cover the opening to close the receiving cavity. Electrode assemblies 52 are encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the battery cell 5 may be one or more, and can be adjusted according to requirements.
[0096] Electrode assemblies typically include positive and negative electrodes. The negative electrode is the electrode that absorbs or lithiates lithium ions during battery charging and releases or delithiates lithium during discharge. The positive electrode is the electrode that releases or delithiates lithium ions during battery charging and absorbs or lithiates lithium during discharge.
[0097] Natural graphite flakes and artificial graphite have long-range ordered layered structures, which are beneficial for improving lithium-ion storage capacity. Therefore, they are often used as negative electrode active materials in existing technologies. However, the long-range ordered layered structure requires lithium ions to be inserted from a specific direction, which limits the insertion rate of lithium ions and makes it difficult to further improve the fast-charging performance of battery cells.
[0098] To address the aforementioned issues, the first aspect of this application provides a battery cell comprising a positive electrode, a negative electrode, and an electrolyte; the negative electrode comprises a negative current collector and a negative electrode film disposed on at least one side of the negative current collector, the negative electrode film comprising a negative electrode active material, the negative electrode active material comprising microcrystalline graphite, and the particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite being 0.5-3.
[0099] Natural flake graphite or artificial graphite has a primary particle size greater than 5 μm and is arranged in an orderly layered manner, such as... Figure 2 As shown, it exhibits anisotropy. Microcrystalline graphite differs from natural flake graphite and artificial graphite, displaying an amorphous or cryptocrystalline structure with a relatively disordered layered arrangement, such as... Figure 1 As shown, it is isotropic, which is beneficial for the uniform insertion of lithium ions from all directions. Unlike the prior art, the battery of this application uses microcrystalline graphite as the negative electrode active material. By utilizing the isotropic characteristics of microcrystalline graphite, the effective end face for lithium ion insertion and extraction is increased, thereby further improving the dynamic performance of the battery cell.
[0100] However, microcrystalline graphite has a wide particle size distribution, and particles of varying sizes easily combine to form dense packings. During cycling, this makes it easy for the electrolyte to be squeezed out, and the recirculation rate is slow, leading to a decrease in battery capacity retention and deterioration of battery cycle stability. In the embodiments of this application, the negative electrode active material includes microcrystalline graphite, and the particle size distribution (Dv90-Dv10) / Dv50 is controlled within the range of 0.5-3, resulting in more uniform microcrystalline graphite size, reducing electrolyte loss, and improving battery cycle performance. Simultaneously, the more uniform size of the microcrystalline graphite helps increase the porosity of the negative electrode film, improving electrolyte wetting and reabsorption, further enhancing the battery's fast-charging performance. In summary, the battery cell of this application exhibits excellent fast-charging and cycle performance.
[0101] According to national standards, microcrystalline graphite refers to an aggregate of natural graphite with a particle size of less than 1 μm. The type of negative electrode active material can be tested using any method known in the art. As an example, scanning electron microscopy is used to observe the cross-section of the negative electrode active material and measure the particle size of the primary particles; graphite with a primary particle size of less than 1 μm is considered microcrystalline graphite. It is worth noting that the material used for testing in this application can be freshly prepared material or material obtained by scraping powder from the electrode sheet.
[0102] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of microcrystalline graphite can be selected as 0.5, 0.7, 1, 1.2, 1.4, 1.6, 1.8, 1.86, 2, 2.1, 2.3, 2.5, 2.7, 2.8, 3 or any value range between the two.
[0103] In this document, Dv10, Dv50, and Dv90 have meanings known in the art, representing the particle size corresponding to a cumulative volume distribution percentage of 10%, 50%, and 90%, respectively.
[0104] The particle size distribution (Dv90-Dv10) / Dv50 of microcrystalline graphite represents the concentration of the microcrystalline graphite particle size distribution. The smaller the value, the more concentrated the microcrystalline graphite particle size distribution.
[0105] Particle size distribution, Dv10, Dv50, and Dv90 can be determined using methods and instruments known in the art. For example, they can be conveniently determined using a laser particle size analyzer, referring to GB / T 19077-2016 Particle Size Distribution by Laser Diffraction. The testing instrument can be the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0106] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of microcrystalline graphite is 0.5-2.
[0107] In this embodiment, the particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is controlled within the above range. The size of the microcrystalline graphite is more uniform, and the porosity of the negative electrode film containing microcrystalline graphite is increased, which helps to further improve the cycle performance and fast charging performance of the battery cell.
[0108] In some embodiments, the orientation degree (OI) of microcrystalline graphite is 0.5-4.
[0109] In some embodiments, the orientation degree OI value of the microcrystalline graphite is 0.5, 0.7, 1, 1.2, 1.4, 1.6, 1.8, 1.86, 2, 2.1, 2.3, 2.5, 2.6, 2.7, 2.8, 3, 3.2, 3.3, 3.5, 3.6, 3.8, 3.9, 4 or any value between the two.
[0110] In this document, the orientation degree (OI) value has a well-known meaning in the art, representing the degree of order in the arrangement of crystals or particles in a material. It can be determined using an orientation degree meter or an X-ray diffractometer, as illustrated below: Using an X-ray diffractometer (such as a Bruker D8 Discover), the test can be performed according to JISK0131-1996 and JB / T 4220-2011. The X-ray diffraction pattern of the material is obtained, and the OI value is calculated using the formula OI value = I004 / I110. I004 is the integrated area of the diffraction peak of the 004 crystal plane of crystalline carbon in the material, and I110 is the integrated area of the diffraction peak of the 110 crystal plane of crystalline carbon in the negative electrode film. In the X-ray diffraction analysis test of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the ray wavelength... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min. The higher the OI value, the higher the degree of order in the material.
[0111] When the OI value of microcrystalline graphite is within the above range, the degree of order of microcrystalline graphite is low, and the content of effective end faces for lithium ion insertion and extraction is high, which is conducive to the uniform insertion of lithium ions from all directions, improves the dynamic performance of the electrode, and enhances the fast charging performance of the battery.
[0112] In some embodiments, the orientation degree (OI) value of microcrystalline graphite is 2-3.
[0113] A high OI value indicates high internal grain order, reducing the effective end faces for lithium-ion insertion / extraction, leading to decreased electrode kinetics and consequently affecting the battery's fast-charging performance. Conversely, a low OI value indicates low internal grain order, increasing side reactions between disordered carbon materials and the electrolyte, thus affecting the battery's cycle performance. In the embodiments of this application, the OI value of the microcrystalline graphite is in the range of 2-3, indicating suitable internal grain order, which helps improve the battery's fast-charging performance while maintaining good cycle performance.
[0114] In some embodiments, the volume distribution particle size Dv99 of the microcrystalline graphite is 20-50 μm, and the volume distribution particle size Dv50 of the microcrystalline graphite is 10-25 μm.
[0115] In some embodiments, the volume distribution particle size Dv99 of the microcrystalline graphite is 20-50 μm, and the volume distribution particle size Dv50 of the microcrystalline graphite is 10-20 μm.
[0116] In some embodiments, the volumetric particle size Dv99 of the microcrystalline graphite can be selected as 20μm, 21μm, 22μm, 23μm, 24μm, 25μm, 26μm, 27μm, 28μm, 29μm, 30μm, 31μm, 32μm, 33μm, 34μm, 35μm, 36μm, 37μm, 38μm, 39μm, 40μm, 42μm, 44μm, 46μm, 48μm, 50μm or any value range between the two.
[0117] In some embodiments, the volumetric particle size Dv50 of the microcrystalline graphite can be selected as 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm, 20μm, 21μm, 22μm, 23μm, 24μm, 25μm or any value range between the two.
[0118] Furthermore, in the embodiments of this application, the Dv50 of the microcrystalline graphite is in the range of 10-20 μm. The reduction in particle size and the increase in specific surface area of the particles help to provide more active sites and shorten the insertion / extraction path, thereby improving the insertion / extraction speed, improving the kinetic performance of the negative electrode sheet, and further improving the fast charging performance of the battery.
[0119] In some embodiments, the graphitization degree of microcrystalline graphite is greater than or equal to 88%.
[0120] In some embodiments, the graphitization degree of microcrystalline graphite is 90%-96%.
[0121] In some embodiments, the degree of graphitization of the negative electrode active material can be selected as 88%, 88.5%, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, or any value range between the two.
[0122] In this document, the degree of graphitization has a meaning known in the art and can be tested using instruments and methods known in the art. For example, it can be tested using an X-ray diffractometer (such as a Bruker D8 Discover), and the testing can be performed with reference to JISK 0131-1996 and JB / T 4220-2011. The average interlayer spacing d002 of the C(002) crystal plane in the material's crystal structure can be obtained, and then the degree of graphitization can be calculated using the formula g = (0.344 - d002) / (0.344 - 0.3354) × 100%. In the above formula, d002 is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure, expressed in nanometers (nm).
[0123] Graphitization degree reflects the integrity of the graphite crystal structure in a material, that is, the regularity of the arrangement of carbon atoms in the graphite structure. High graphitization degree indicates small interlayer spacing, smaller lattice rotation, less random stacking of layers, and a more ordered arrangement, resulting in high specific capacity. Low graphitization degree indicates large interlayer spacing, which is beneficial for rapid lithium-ion insertion / extraction, improving the rate performance of the battery. Furthermore, large interlayer spacing results in less material expansion during lithium insertion, leading to a shallow charge / discharge effect. Additionally, low graphitization degree reduces the amount of splined carbon atoms in the graphite material. 3 The abundance of bonds in graphite materials creates inter-layer constraints, resulting in a more stable structure and excellent stability during cycling, which is beneficial for long-term cycling. In the embodiments of this application, the degree of graphitization of the microcrystalline graphite is within the above-mentioned range, which is beneficial for improving the cycle performance of the battery cells.
[0124] In some implementations, the oil absorption value of microcrystalline graphite is less than or equal to 65.
[0125] In some implementations, the oil absorption value of microcrystalline graphite is 55-60.
[0126] In some embodiments, the oil absorption value of microcrystalline graphite can be selected as 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 64.5, 64, 64.5, 65 or any range between the two.
[0127] In this document, the oil absorption value refers to the volume of linseed oil that 100g of material can absorb. For example, an oil absorption value of 40ml / 100g means that 100g of material can absorb 40ml of linseed oil. Testing can be performed using methods and equipment known in the art, as illustrated below: Obtain test oil and material samples separately, and set the torque threshold of the oil absorption value tester; add oil at a constant rate to the sample in the mixing chamber of the oil absorption value tester. As the amount of oil absorbed by the sample increases, the viscosity of the sample-oil mixture continuously increases. When the viscosity of the mixture reaches the preset torque threshold of the oil absorption value tester, stop and calculate the volume of oil absorbed per unit mass of sample; this value is the oil absorption value QI of the sample. The test oil is linseed oil (DBP), and the torque threshold is 1N.
[0128] The oil absorption value of a material is mainly related to its specific surface area, surface properties, particle shape, and particle size distribution. The oil absorption value of the negative electrode active material reflects its dispersibility in the negative electrode slurry. A low oil absorption value indicates excellent dispersibility in the negative electrode slurry, which in turn provides excellent resistance to sedimentation and dispersion. This facilitates control of the coating weight during electrode coating, resulting in negative electrode sheets with uniform distribution and thickness of the active material. It also reduces the possibility of uneven local current density during charging and discharging, minimizes lithium plating caused by electrode polarization, and improves battery cycle performance. In conclusion, microcrystalline graphite with a suitable oil absorption value range is beneficial for improving the cycle performance of individual battery cells.
[0129] In some embodiments, the negative electrode film layer includes a first negative electrode film layer disposed near the negative electrode current collector side and a second negative electrode film layer disposed away from the negative electrode current collector side of the first negative electrode film layer. The first negative electrode film layer includes a first negative electrode active material, which includes microcrystalline graphite with a particle size distribution (Dv90-Dv10) / Dv50 of 0.5-3.
[0130] Microcrystalline graphite exhibits superior lithium intercalation kinetics due to its isotropic properties. Placing a first negative electrode film containing microcrystalline graphite on the current collector side helps increase the driving force for lithium ions to migrate from the electrolyte to the current collector side, improves the diffusion rate and reabsorption rate of lithium ions in the negative electrode film, and enhances the battery's kinetic performance and cycle stability.
[0131] In some embodiments, the porosity of the first negative electrode film layer is 12%-30%.
[0132] In some embodiments, the porosity of the first negative electrode film layer is 18%-28%.
[0133] In some embodiments, the porosity of the first negative electrode film layer may be selected as 12%, 15%, 20%, 21%, 22%, 23%, 24%, 24.1%, 24.5%, 25%, 25.6%, 25.8%, 26%, 26.5%, 26.7%, 27%, 27.1%, 28%, 28.3%, 29%, 30%, or any value range between the two.
[0134] In this application, porosity has a meaning known in the art. The porosity of the first negative electrode film layer can be determined using methods and instruments known in the art, as exemplified below: Following the preparation parameters of the first negative electrode film layer in the embodiment, a negative electrode sheet containing only the first negative electrode film layer is prepared. The negative electrode sheet is then cut into small circular samples of a certain area. The volume V of the negative electrode current collector and the volume V1 of the negative electrode sheet are calculated. Referring to GB / T24586-2009, an inert gas (such as helium or nitrogen) is used as the medium, and the gas replacement method is employed. The true volume V2 of the negative electrode film layer is measured using a true density meter. The porosity of the negative electrode film layer = (V1-V2) / (V1-V) x 100%. Multiple negative electrode film layer samples (e.g., 30 pieces) with good appearance and no powder shedding at the edges can be tested, and the average value of the results is taken, thereby improving the accuracy of the test results. The testing instrument can be a Micromeritics AccuPycⅡ1340 true density meter.
[0135] The negative electrode film layer near the current collector typically has a lower electrolyte wetting rate, thereby reducing the contact area between the electrolyte and the negative electrode active material and affecting the battery's fast-charging performance. In this embodiment, the first negative electrode film layer is close to the current collector and has a higher porosity, which helps to improve the electrolyte wetting rate of the negative electrode film layer near the current collector, thereby improving the battery's fast-charging performance.
[0136] In some embodiments, the OI value of the first negative electrode film is 1-4.
[0137] In some embodiments, the OI value of the first negative electrode film can be selected as 1, 2, 2.3, 3, 3.3, 3.5, 4 or any value range between the two.
[0138] In this document, the OI value has a known meaning in the art. The OI value of the first negative electrode film can be tested using methods and instruments known in the art, as shown in the following example: Following the preparation parameters of the first negative electrode film in the embodiment, a negative electrode sheet containing only the first negative electrode film is prepared. The OI value is then tested using an X-ray diffractometer (such as a Bruker D8 Discover). The testing can be referenced in JISK0131-1996 and JB / T 4220-2011. The X-ray diffraction pattern of the negative electrode film is obtained. According to OI value = I... 004 / I 110 The OI value of the negative electrode film was calculated. 004 I is the integrated area of the diffraction peaks of the crystalline carbon 004 crystal plane in the negative electrode film. 110 This represents the integrated area of the peak on the 110 crystal plane of the crystalline carbon in the negative electrode film. In the X-ray diffraction analysis of this application, a copper target can be used as the anode target, with CuKα rays as the radiation source, and the ray wavelength... The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min.
[0139] The OI value indicates the degree of order in the arrangement of crystals or particles in a material. A higher OI value indicates a more ordered arrangement of particles or molecules in the material; a lower OI value indicates a more disordered orientation of the material. The OI value of the first negative electrode film layer in the embodiments of this application is within the above range, and the disorder of the first negative electrode film layer is low, which helps to increase the number of lithium-ion insertion / extraction end faces, improve the dynamic performance of the electrode, and thus improve the fast charging performance of the battery.
[0140] In some embodiments, the OI value of the first negative electrode film is 2-3.
[0141] A high OI value indicates high material order, fewer effective lithium-ion insertion / extraction faces, and decreased electrode kinetics, thus affecting the battery's fast-charging performance. Conversely, a low OI value indicates low material order, high porosity of the negative electrode film, increased electrolyte wetting, and increased side reactions, thus affecting the battery's cycle performance. In the embodiments of this application, the orientation degree OI value of the first negative electrode film is in the range of 2-3, indicating suitable material order, which helps improve the battery's fast-charging performance while also ensuring good cycle performance.
[0142] In some embodiments, the second negative electrode film layer includes a second negative electrode active material, which includes one or more of natural flake graphite and artificial graphite.
[0143] In some embodiments, the second negative electrode film layer includes a second negative electrode active material, which includes artificial graphite.
[0144] In some embodiments, the second negative electrode film layer includes a second negative electrode active material, which includes natural flake graphite.
[0145] Natural flake graphite and artificial graphite have good cycle stability. The second negative electrode film layer in the embodiments of this application includes one or more of natural flake graphite or artificial graphite, which helps to further improve the cycle performance of the battery.
[0146] In some embodiments, the orientation degree (OI) of natural flake graphite is 4.5-10.
[0147] In some embodiments, the orientation degree OI value of natural flake graphite can be selected as 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or any range between the two.
[0148] In some embodiments, the orientation degree (OI) value of the artificial graphite is 5-12.
[0149] In some embodiments, the orientation degree OI value of the artificial graphite can be selected as 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12 or any range between the two.
[0150] If the orientation degree (OI) value of natural or artificial graphite is within the above range, it indicates that it is anisotropic compared to microcrystalline graphite, which is not conducive to lithium ion insertion from all directions, but can improve battery capacity.
[0151] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 8-25 μm.
[0152] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 10-20 μm.
[0153] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material can be selected as 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm or any value range between the two.
[0154] In some embodiments, the volume distribution particle size Dv99 of the second negative electrode active material is 25-45 μm.
[0155] In some embodiments, the volume distribution particle size Dv99 of the second negative electrode active material is 27-40 μm.
[0156] In some embodiments, the volume distribution particle size Dv99 of the second negative electrode active material can be selected as 25μm, 27μm, 28μm, 29μm, 30μm, 32μm, 34μm, 36μm, 38μm, 40μm, 42μm, 44μm, 45μm or any value range between the two.
[0157] The volume distribution particle size of the second negative electrode active material is within the above range (Dv50, Dv99), and the battery cell has good fast charging performance and energy density.
[0158] In some embodiments, the porosity of the second negative electrode film is 15%-25%.
[0159] In some embodiments, the porosity of the second negative electrode film is 17%-24%.
[0160] In some embodiments, the porosity of the second negative electrode film can be selected as 15%, 17%, 19%, 20%, 21%, 21.5%, 22%, 23%, 24%, 25%, or any value range between the two.
[0161] The porosity of the second negative electrode film can be tested using methods known in the art, as shown in the following example: according to the preparation parameters of the second negative electrode film in the embodiment, a negative electrode sheet containing only the second negative electrode film is prepared, and the porosity is tested using the same method as the first negative electrode film.
[0162] Controlling the porosity of the second negative electrode film within the above range can match the porosity of the first negative electrode film while taking into account the capacity of the negative electrode film, which helps to improve the fast charging performance of the battery while also taking into account the energy density.
[0163] In some embodiments, the OI value of the second negative electrode film is 5-13.
[0164] In some embodiments, the OI value of the second negative electrode film is 5-10.
[0165] In some embodiments, the OI value of the second negative electrode film can be selected as 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5, 12, 12.5, 13 or any range between the two.
[0166] The OI value of the second negative electrode film can be tested together with methods known in the art, as shown in the following example: according to the preparation parameters of the second negative electrode film in the embodiment, a negative electrode sheet containing only the second negative electrode film is prepared, and the OI value of the first negative electrode film is tested in accordance with the testing method.
[0167] In some embodiments, the thickness ratio of the first negative electrode film layer and the second negative electrode film layer is 2:8-5:5.
[0168] In some embodiments, the thickness ratio of the first negative electrode film layer and the second negative electrode film layer is 4:6-5:5.
[0169] In some embodiments, the thickness ratio of the first negative electrode film layer and the second negative electrode film layer can be selected as 2:8, 2.5:7.5, 3:6, 3.5:6.5, 4:6, 4.5:5.5 or any range between the two.
[0170] In this study, the thickness ratio of the first and second negative electrode films can be tested using methods and instruments known in the art, as illustrated below: The negative electrode sheet is cut into 2cm x 2cm samples. The sheet is fixed to the sample stage using paraffin wax, and the stage is then locked in place within a sample holder. The argon ion cross-section polisher (e.g., IB-19500CP) is powered on and evacuated to 104 Pa. The argon flow rate is set to 0.15 MPa, the voltage to 8 kV, and the polishing time to 2 hours. The sample stage is adjusted to swing mode for polishing. After polishing, the sample is tested using a scanning electron microscope (SEM) according to JY / T010-1996. To ensure the accuracy of the test results, multiple (e.g., 10) different regions can be randomly selected from the sample for scanning and testing. Images are taken at a certain magnification (e.g., 5000x), and the thicknesses of the first and second negative electrode films in the test areas are read. The average of the test results from multiple test areas is taken as the average thickness of the first and second negative electrode films.
[0171] In this embodiment, controlling the thickness ratio of the first negative electrode film layer and the second negative electrode film layer within the above-mentioned range helps to improve the fast charging performance of the battery, while also helping to balance cycle performance and energy density.
[0172] In some embodiments, the thickness of the negative electrode film is 80-160 μm.
[0173] In some embodiments, the thickness of the negative electrode film is 100-150 μm.
[0174] In some embodiments, the thickness of the negative electrode film can be selected from 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm or any value range between the two.
[0175] The thickness of the negative electrode film can be measured using a micrometer (e.g., Mitutoyo 293-100, with an accuracy of 0.1 μm).
[0176] In this embodiment of the application, when the ratio of the single-sided thickness of the negative electrode film to the thickness of the negative electrode current collector is within the above range, the fast charging performance of the battery can be further improved while taking into account the energy density.
[0177] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of the battery cell is 1.6 g / cm³. 3 -1.85g / cm 3 .
[0178] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of the battery cell is 1.65 g / cm³. 3 -1.75g / cm 3 .
[0179] In some embodiments, the compaction density of the negative electrode film layer in a fully discharged state of a single battery cell can be selected as 1.6 g / cm³. 3 1.65g / cm 3 1.7g / cm 3 1.75g / cm 3 1.8g / cm 3 1.85g / cm 3 Or the range of values between any two.
[0180] When used in this article, "fully discharged state" refers to the state after placing the battery in a 25°C oven environment, letting it stand for 2 hours, maintaining the battery temperature at 25°C, discharging the battery at a constant current of 1 / 3C to 2.8V, and then discharging it at a constant current of 0.04C to 2.8V.
[0181] The compaction density of the negative electrode film can be tested using methods and instruments known in the art. As an example, the battery is disassembled in a fully discharged state. The negative electrode sheet is cleaned three times or more with a solvent such as dimethyl carbonate (DMC) and dried. A negative electrode sample with an area of S is weighed using an electronic balance, and the weight is recorded as W1. The thickness T1 of the negative electrode sheet is measured using a micrometer. Then, the weighed electrode film is wiped off, and the weight of the negative current collector is measured, recorded as W2. The thickness T2 of the negative current collector is measured using a micrometer. The compaction density of the negative electrode film is then calculated as PD = (W1 - W2) / [(T1 - T2) × S].
[0182] When a battery cell is fully discharged, the compaction density of the negative electrode film is within the above-mentioned range, which is beneficial to improving the energy density of the battery cell.
[0183] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0184] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0185] In addition, this application also provides an electrical device that uses a battery as a power source, the electrical device including at least one of the lithium-ion secondary battery, battery module, or battery pack provided in this application. The lithium-ion secondary battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0186] As the electrical device, a secondary battery, battery module, or battery pack can be selected according to its usage requirements.
[0187] Figure 8 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery for this device, a battery pack or battery module can be used.
[0188] Another example of an electrical device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can use rechargeable batteries as their power source.
[0189] This application also provides an energy storage device that uses a battery as a power source. The energy storage device can be, but is not limited to, an energy storage container, an energy storage cabinet, an energy storage power station, an energy storage battery pack, or a portable energy storage system.
[0190] Example
[0191] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0192] I. Preparation Method
[0193] Example 1
[0194] (1) Preparation of negative electrode sheet
[0195] Preparation of the first negative electrode active material: The original microcrystalline graphite with an orientation degree OI value of 2.6 was crushed using an air jet mill. The feed rate of the air jet mill was adjusted to 2 kg / min and the air flow rate to 10 L / s to obtain the microcrystalline graphite precursor. Then, the microcrystalline graphite precursor was sieved through a 250-mesh sieve to obtain the first negative electrode active material with a particle size distribution of 4-50 μm.
[0196] Preparation of the first negative electrode slurry: The above-mentioned first negative electrode active material, binder (polyvinyl alcohol), and conductive agent (SP-Li) are dissolved in deionized water at a mass ratio of 90:5:5, and then thoroughly ball-milled and mixed to prepare the first negative electrode slurry.
[0197] Preparation of the second negative electrode slurry: Artificial graphite, binder (polyvinyl alcohol), and conductive agent (SP-Li) are dissolved in deionized water at a mass ratio of 90:5:5, and then thoroughly ball-milled and mixed to prepare the negative electrode slurry.
[0198] The first negative electrode slurry and the second negative electrode slurry are simultaneously extruded using a dual-cavity coating device. The first negative electrode slurry is coated onto the copper foil current collector to form the first negative electrode film layer, and the second negative electrode slurry is coated onto the first negative electrode film layer to form the second negative electrode film layer. The negative electrode current collector coated with slurry is dried at room temperature and then transferred to an oven for drying. After cold pressing and slitting, the negative electrode sheet is obtained.
[0199] The first negative electrode active material has an oil absorption value of 57 and a graphitization degree of 94.3%; the artificial graphite has an OI value of 7.2, a Dv50 of 16 μm, and a Dv99 of 38 μm; the porosity of the first negative electrode film is 26.5%, and the porosity of the second negative electrode film is 21.5%; the thickness ratio of the first negative electrode film to the second negative electrode film is 4:6; the thickness of the negative electrode film is 125 μm; and the compaction density of the negative electrode film in a fully discharged state is 1.68 g / cm³. 3 .
[0200] (2) Preparation of positive electrode sheet
[0201] The positive electrode active material (LiNi) 0.9 Co 0.05 Mn 0.05 O2), conductive super carbon black, and polyvinylidene fluoride (PVDF) are dissolved in NMP (N-methylpyrrolidone) solvent at a mass ratio of 93:5:1. The mixture is thoroughly stirred and mixed evenly, and then wetted, kneaded and dispersed to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector, and then dried, cold-pressed and cut to obtain the positive electrode sheet.
[0202] (3) Preparation of electrolyte
[0203] In an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed uniformly in a volume ratio of 1:1:1. A certain amount of lithium LiPF6 was dissolved in the organic solvent, and the concentration of the lithium salt was controlled at 1 mol / L. Then, 1% by weight of iminoselenourea compound was added and stirred evenly to obtain the electrolyte.
[0204] (4) Separating membrane
[0205] A polyethylene film with a thickness of 13 μm.
[0206] (5) Battery manufacturing
[0207] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The electrodes are then wound to obtain the electrode assembly. The electrode assembly is placed in a battery casing, dried, and then injected with the electrolyte. Following formation and settling processes, a lithium-ion battery is produced.
[0208] Examples 2-4
[0209] The preparation method of the lithium-ion battery is similar to that of Example 1, except that the mesh size of the sieve is adjusted. Specifically, Example 2 uses a 400-mesh sieve, Example 3 uses a 150-mesh sieve, and Example 4 uses a 100-mesh sieve, so that the particle size distribution (Dv90-Dv10) / Dv50, Dv50, Dv99 of the microcrystalline graphite in the first negative electrode film layer is different, as detailed in Table 1.
[0210] Examples 5-6
[0211] The preparation method of the lithium-ion battery is similar to that in Example 1, except that the feed rate and airflow rate of the airflow crusher are adjusted, so that the Dv50 and Dv99 of the microcrystalline graphite in the first negative electrode film are different, as detailed in Table 1.
[0212] Example 7
[0213] The preparation method of the lithium-ion battery is similar to that in Example 1, except that the orientation degree OI value of the original microcrystalline graphite is 1, which makes the orientation degree OI value of the microcrystalline graphite in the first negative electrode film layer different, as detailed in Table 1.
[0214] Example 8
[0215] The preparation method of the lithium-ion battery is similar to that in Example 1, except that it does not contain a second negative electrode film layer, as detailed in Table 1.
[0216] Example 9
[0217] The preparation method of the lithium-ion battery is similar to that in Example 8, except that the orientation degree OI value of the original microcrystalline graphite is 3.5, which makes the orientation degree OI value of the microcrystalline graphite in the first negative electrode film layer different, as detailed in Table 1.
[0218] Example 10
[0219] The preparation method of the lithium-ion battery is similar to that in Example 1, except that the second negative electrode active material is different. The artificial graphite in the second slurry preparation process is replaced with natural flake graphite, which has an orientation degree OI value of 6.7, as detailed in Table 1.
[0220] Comparative Example 1
[0221] The preparation method of the lithium-ion battery is similar to that in Example 1, except that the mesh size of the sieve is adjusted. Specifically, a 50-mesh sieve is used so that the (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 4, Dv50 is 8μm, and Dv99 is 36μm, as detailed in Table 1.
[0222] Comparative Example 2
[0223] The preparation method of the lithium-ion battery is similar to that of Comparative Example 1, except that it does not contain a second negative electrode film layer, as detailed in Table 1.
[0224] Comparative Example 3
[0225] The preparation method of the lithium-ion battery is similar to that of Example 10, except that it does not contain a first negative electrode film layer, as detailed in Table 1.
[0226] II. Performance Testing
[0227] 1. Cyclic capacity retention
[0228] At 25°C, charge the battery to 4.25V at a charging rate of 0.33C (the nominal capacity), then charge it to 0.05C at a constant voltage of 4.25V, let it stand for 10 minutes, and then discharge it to 2.8V at a discharging rate of 1C, let it stand for 10 minutes. This one charge-discharge cycle is one cycle. The ratio of the battery capacity to the nominal capacity after the 1000th charge-discharge cycle is the cycle capacity retention rate.
[0229] 2. Battery fast charging performance test (charging time test):
[0230] ① Voltage calibration: 1) The positive electrode, negative electrode, separator, and electrolyte in the example or comparative example are used to prepare a stacked three-electrode battery, and it is placed at 25°C for 30 min; 2) At 25°C, the battery cells are charged at 0.33C to the charging cutoff voltage of 4.25V, and then constant voltage charging is continued at the charging cutoff voltage until the current is 0.05C, and the charging is cut off (where C represents the rated capacity of the battery cell); 3) Place it at 25°C for 1 h; 4) At 25°C, the battery cells are discharged at 0.33C to the discharge cutoff voltage of 2.8V, and the total discharge capacity C0 of the battery cells is recorded; 5) Place it at 25°C for 1 h.
[0231] ② Room temperature charging test: 1) Prepare a stacked three-electrode battery using the positive electrode, negative electrode, separator, and electrolyte from the examples or comparative examples, and let it stand for 30 minutes; 2) Discharge with 0.33C0 DC to the discharge cutoff voltage of 2.8V, at which point the SOC is 0%; 3) Let it stand for 5 minutes; 4) Charge with 5C0 constant current until the negative electrode potential is 0V, and read the capacity C1 at this point, which corresponds to C1 / C0SOC; 5) Let it stand for 5 minutes; 6) Charge with 4.5C0 constant current until the negative electrode potential is 0V, and read the capacity C2 at this point, which corresponds to C2 / C0SOC; 7) Let it stand for 5 minutes; 8) Charge with 4C0 constant current until the negative electrode potential is 0V, and read the capacity C3 at this point, which corresponds to C3 / C0SOC; 9) Let it stand for 5 minutes; 10) Charge with 3C0 constant current until the negative electrode potential is 0V, and read the capacity C4 at this point. 11) Let stand for 5 minutes; 12) Charge with 2C0 at a constant current until the negative electrode potential is 0V, and read the capacity C5 at this time, which corresponds to C5 / C0SOC; 13) Let stand for 5 minutes; 14) Charge with 1C0 at a constant current until the negative electrode potential is 0V, and read the capacity C6 at this time, which corresponds to C6 / C0SOC; 15) Let stand for 5 minutes; 16) Charge with 0.8C0 at a constant current until the negative electrode potential is 0V, and read the capacity C7 at this time, which corresponds to C7 / C0SOC; 17) Let stand for 5 minutes; 16) Charge with 0.5C0 at a constant current until the negative electrode potential is 0V, and read the capacity C8 at this time, which corresponds to C8 / C0SOC; 15) Let stand for 5 minutes; 16) Charge with 0.33C0 at a constant current until the negative electrode potential is 0V, and read the capacity C9 (i.e., C0), which corresponds to 100%SOC. The required charging time is obtained by summing the total charging time from 10% SOC to 80% SOC.
[0232] III. Test Results
[0233] The test results of the above embodiments and comparative examples are shown in Table 1.
[0234] Table 1
[0235]
[0236] Note: " / " indicates that the substance was added or not tested.
[0237] A comparison of Examples 1-10 and Comparative Examples 1-3 shows that the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a negative electrode active material, which includes microcrystalline graphite. The particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 0.5-3, which is beneficial to improving the cycle performance and fast charging performance of the battery.
[0238] A comparison of Examples 1-2 and Examples 3-4 shows that the particle size distribution (Dv90-Dv10) / Dv50 of microcrystalline graphite in the range of 0.5-2 helps to further improve the cycle performance and fast charging performance of the battery.
[0239] A comparison of Examples 1, 5, and 6 shows that the volume distribution particle size Dv50 of microcrystalline graphite is in the range of 10-20 μm, which helps to further improve the fast charging performance of battery cells.
[0240] A comparison of Examples 1 and 7, and Examples 8 and 9, shows that the orientation degree OI value of the first negative electrode film layer is in the range of 2-3, which helps to further improve the fast charging performance of the battery while taking into account the cycle performance.
[0241] Compared with Examples 1, 8, and 10, the negative electrode film layer includes a first positive electrode film layer and a second positive electrode film layer. The second negative electrode film layer includes one or more of natural flake graphite or artificial graphite, which helps to further improve the cycle performance of the battery.
[0242] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A battery cell, characterized in that, It includes positive electrode, negative electrode, and electrolyte; The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector. The negative electrode film layer includes a negative electrode active material, which includes microcrystalline graphite. The particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 0.5-3.
2. The battery cell according to claim 1, characterized in that, The particle size distribution (Dv90-Dv10) / Dv50 of the microcrystalline graphite is 0.5-2.
3. The battery cell according to claim 1 or 2, characterized in that, The orientation degree (OI) of the microcrystalline graphite is 0.5-4, and can be selected as 2-3.
4. The battery cell according to any one of claims 1-3, characterized in that, The microcrystalline graphite has a volume distribution particle size Dv99 of 20-50 μm and a volume distribution particle size Dv50 of 10-25 μm, optionally with a volume distribution particle size Dv50 of 10-20 μm.
5. The battery cell according to any one of claims 1-4, characterized in that, The graphitization degree of the microcrystalline graphite is greater than or equal to 88%, and can be selected as 90%-96%; and / or, the oil absorption value of the microcrystalline graphite is less than or equal to 65, and can be selected as 55-60.
6. The battery cell according to any one of claims 1-5, characterized in that, The negative electrode film layer includes a first negative electrode film layer disposed near the negative electrode current collector side and a second negative electrode film layer disposed on the side of the first negative electrode film layer away from the negative electrode current collector side. The first negative electrode film layer includes a first negative electrode active material, which includes the microcrystalline graphite.
7. The battery cell according to claim 6, characterized in that, The porosity of the first negative electrode film layer is 12%-30%, and can be selected as 18%-28%.
8. The battery cell according to claim 6 or 7, characterized in that, The OI value of the first negative electrode film is 1-4, and can be selected as 2-3.
9. The battery cell according to any one of claims 6-8, characterized in that, The second negative electrode film layer includes a second negative electrode active material, which includes one or more of natural flake graphite and artificial graphite.
10. The battery cell according to claim 9, characterized in that, The orientation degree OI value of the natural flake graphite is 4.5-10; the orientation degree OI value of the artificial graphite is 5-12.
11. The battery cell according to claim 9 or 10, characterized in that, The volume distribution particle size Dv50 of the second negative electrode active material is 8-25 μm, optionally 10-20 μm; and / or, the volume distribution particle size Dv99 of the second negative electrode active material is 25-45 μm, optionally 27-40 μm.
12. The battery cell according to any one of claims 6-11, characterized in that, The porosity of the second negative electrode film is 15%-25%, and can be selected as 17%-24%.
13. The battery cell according to any one of claims 6-12, characterized in that, The OI value of the second negative electrode film is 5-13, and can be selected as 5-10.
14. The battery cell according to any one of claims 6-13, characterized in that, The thickness ratio of the first negative electrode film layer to the second negative electrode film layer is 2:8-5:5, and can be selected as 4:6-5:
5.
15. The battery cell according to any one of claims 1-14, characterized in that, The thickness of the negative electrode film is 80-160 μm, and can be selected as 100-150 μm.
16. The battery cell according to any one of claims 1-15, wherein the compaction density of the negative electrode film layer in the fully discharged state is 1.6 g / cm³. 3 -1.85g / cm 3 The option is 1.65g / cm³. 3 -1.75g / cm 3 .
17. A battery device, characterized in that, The battery device comprises the battery cell according to any one of claims 1 to 16.
18. An electrical appliance, characterized in that, The electrical device includes the battery device as described in claim 17, the battery device being used to provide electrical energy.
19. An energy storage device, characterized in that, The energy storage device includes the battery device as described in claim 17, the battery device being used to store electrical energy.